2013
DOI: 10.1002/ece3.603
|View full text |Cite
|
Sign up to set email alerts
|

Did southern Western Ghats of peninsular India serve as refugia for its endemic biota during the Cretaceous volcanism?

Abstract: The Western Ghats (WG) of south India, a global biodiversity hotspot, has experienced complex geological history being part of Gondwana landmass and encountered extensive volcanic activity at the end of Cretaceous epoch. It also has a climatically and topographically heterogeneous landscape. Thus, the WG offer a unique setting to explore the influence of ecological and geological processes on the current diversity and distribution of its biota. To this end, three explicit biogeographical scenarios were hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…These hypothetical processes, examined using phylogenetic reconstructions combined with fossil-calibrated molecular dating techniques, help to advance our understanding of the historical assembly, by revealing alternative lineage accumulation through time. It has been reported that Southern Western Ghats have served as such a refuge during Deccan volcanism for scolopendrid centipede genus Digitipes, a taxon confined to wet evergreen forests and the taxa commenced their range expansion to the northern areas of the Western Ghats in the post-volcanic periods in the Paleocene (Joshi and Karanth, 2013).…”
Section: Sw Sri Lanka As a Floristic Refugiummentioning
confidence: 99%
See 3 more Smart Citations
“…These hypothetical processes, examined using phylogenetic reconstructions combined with fossil-calibrated molecular dating techniques, help to advance our understanding of the historical assembly, by revealing alternative lineage accumulation through time. It has been reported that Southern Western Ghats have served as such a refuge during Deccan volcanism for scolopendrid centipede genus Digitipes, a taxon confined to wet evergreen forests and the taxa commenced their range expansion to the northern areas of the Western Ghats in the post-volcanic periods in the Paleocene (Joshi and Karanth, 2013).…”
Section: Sw Sri Lanka As a Floristic Refugiummentioning
confidence: 99%
“…Consequently, such refugial hotspots of biological diversity are indeed among the best laboratories for identification of and analysis for conservation through prioritized phylogeographic research (Couvreur et al, 2008, Joshi andKaranth, 2013).…”
Section: Sw Sri Lanka As a Floristic Refugiummentioning
confidence: 99%
See 2 more Smart Citations
“…Although no systematic studies have been conducted comparing species of differing ecologies and dispersal abilities, an impact of this Gap has also been found in small, restricted species like frogs [33] and some plants [34] and even in large-bodied, wide-ranging species like elephants [35]. However, certain older taxa like centipedes [36] and some long-lived trees [37] do not appear to be affected by this Gap. Although the Shenkottah and the Palghat Gaps are geologically very old ( pre-Cambrian), the impact on recent and relatively vagile colonizers like birds, especially those with small ranges, is likely to be through more recent climatic effects [38].…”
Section: (A) Nested Patterns Of Divergences In Time and Spacementioning
confidence: 99%